Clinical and metabolic correlates of cerebral calcifications in Sturge–Weber syndrome - Pilli, Vinod K (Dev Med Child Neurol, 2017)
AIM: To evaluate clinical and metabolic correlates of cerebral calcifications in children with Sturge–Weber syndrome (SWS). METHOD: Fifteen children (11 female, 4 male; age range 7mo–9y 0mo, mean 4y 1mo) with unilateral SWS underwent baseline and follow-up magnetic resonance imaging (MRI) with susceptibility weighted imaging (SWI), glucose metabolism positron emission tomography (PET), and neurocognitive assessment (mean follow-up 1y 7mo). Calcified brain volumes measured on SWI were correlated with areas of abnormal glucose metabolism, seizure variables, and cognitive function (intelligence quotient [IQ]). RESULTS: Ten children had brain calcification at baseline and 11 at follow-up. Mean calcified brain volume increased from 1.67 to 2.7cm(3) (p=0.003) in these children; the rate of interval calcified volume increase was associated with early onset of epilepsy (Spearman's rho [r(s)]=–0.63, p=0.036). Calcified brain regions showed a variable degree of glucose hypometabolism with the metabolic abnormalities often extending to non-calcified cerebral lobes. Larger calcified brain volumes at baseline were associated with longer duration of epilepsy (r(s)=0.69, p=0.004) and lower outcome IQ (r(s)=–0.53, p=0.042). INTERPRETATION: Brain calcifications are common and progress faster in SWS children with early epilepsy onset, and are associated with a variable degree of hypometabolism, which is typically more extensive than the calcified area. Higher calcified brain volumes may indicate a risk for poorer neurocognitive outcome.